Inflexive Marker and Morphophonological Processes in the Lamalera Dialect of Lamaholot Language (LDLL) - Yosef Demon; Veronika Genua (Randwick International of Education and Linguistics Science Journal, 2021)
Inflection is a universal linguistic phenomenon. The phenomenon of inflection occurs in every language according to each language system. The language system of each language greatly determines the peculiarities of the language inflection. Inflection in a language that is agglutinative is different from that in a language that has a synthetic, tonal and isolating system. The treatment of each language is different for this case of inflection. Lamalera Dialect of Lamaholot Language (LDLL) also shows inflection. Inflection in LDLL is different from inflection in other languages ​​because of the language system, especially the LDLL sound system. LDLL is not characterized by agglutinative, nor synthetic, tonal nor isolating morphology. What is the strategy for inflection in LDLL? The result of the study shows that in LDLL, inflection is expressed clitically on the verb. These clitics are cross-referenced by the verbs. There are two types of cross-reference clitics, namely cross-referencing proclitics and enclitics. Proclitic cross-referencing applies to both transitive and intransitive root verbs. This form of cross-referencing pronouns is both proclitic and enclitic, and morphophonological changes actually occur. This process cannot be avoided because morphophonological processes actually occur due to merging of the morpheme with another morpheme. In this case the clitic is considered as bound morpheme.